Development and validation of a UPLC-MS/MS assay for the determination of gemcitabine and its L-carnitine ester derivative in rat plasma and its application in oral pharmacokinetics - Gang Wang; Dongyang Zhao; Hongxiang Chen; Dawei Ding; Longfa Kou; Lifang Sun; Chenxia Hao; Xincong Li; Kai Jia; Qiming Kan; Xiaohong Liu; Zhonggui He; et al. (Elsevier, 2017)
A simple and rapid UPLC-MS/MS method to simultaneously determine gemcitabine and its L-carnitine ester derivative (2'-deoxy-2', 2'-difluoro-N-((4-amino-4-oxobutanoyl) oxy)-4-(trimethyl amm-onio) butanoate-cytidine, JDR) in rat plasma was developed and validated. The conventional plasma sample preparation method of nucleoside analogues is solid-phase extraction (SPE) which is time-consuming and cost-expensive. In this study, gradient elution with small particles size solid phase was applied to effectively separate gemcitabine and JDR, and protein precipitation pretreatment was adopted to remove plasma protein and extract the analytes with high recovery(>81%). Method validation was performed as per the FDA guidelines, and the standard curves were found to be linear in the range of 5-4000 ng/ml for JDR and 4-4000 ng/ml for gemcitabine, respectively. The lower limit of quantitation (LLOQ) of gemcitabine and JDR was 4 and 5 ng/ml, respectively. The intra-day and inter-day precision and accuracy results were within the acceptable limits. Finally, the developed method was successfully applied to investigate the pharmacokinetic studies of JDR and gemcitabine after oral administration to rats.